Administration of protopine prevents mitophagy and acute lung injury in sepsis - Xiao, Zhong; Long, Juan; Zhang, Jie; Qiu, Zhimin; Zhang, Chen; Liu, Hongbing; Liu, Xinyong; Wang, Kang; Tang, Yahui; Chen, Longwang; Lu, Zhongqiu; Zhao, Guangju (Frontiers in Pharmacology, 2023)
Sepsis is a severe life-threatening infection that induces a series of dysregulated physiologic responses and results in organ dysfunction. Acute lung injury (ALI), the primary cause of respiratory failure brought on by sepsis, does not have a specific therapy. Protopine (PTP) is an alkaloid with anti-inflammatory and antioxidant properties. However, the function of PTP in septic ALI has not yet been documented. This work sought to investigate how PTP affected septic ALI and the mechanisms involved in septic lung damage, including inflammation, oxidative stress, apoptosis, and mitophagy. Results showed that the septic lung pathological alterations were significantly reversed by PTP. Meanwhile, in mice with ALI induced by cecal ligation and puncture (CLP) and in BEAS-2B cells with lipopolysaccharide (LPS) exposure, inflammation, oxidative stress, pulmonary apoptosis, and mitophagy were downregulated after PTP treatment. The research shows that PTP prevents excessive mitophagy and ALI in sepsis, suggesting that PTP has a potential role in the therapy of sepsis.